Development of a plasma electroacoustic actuator for active noise control applications. (23rd September 2020) - Sergeev, S; Lissek, H; Howling, A; Furno, I; Plyushchev, G; Leyland, P
Abstract: Conventional loudspeakers generate sound through the vibration of a diaphragm, attached to a rigid frame through elastic suspensions. Although such construction is satisfactory for sound diffusion in steady environments, it is likely to fail in harsh conditions, which is often the case for active noise control applications. Plasma-based actuators appear to be a promising alternative since they do not involve any fragile moving parts. In this paper, a positive corona discharge actuator in a wire-to-mesh geometry is proposed in the perspective of active noise control applications, as it is capable of generating sufficient sound pressure levels with limited signal distortion. The study introduces analytical and numerical models aiming at characterizing the sound field generated by the corona discharge actuator. The numerical simulation can facilitate the designing of such transducers. The acoustic power of the experimental prototype is increased through the optimization of emitter wires arrangement. The comparison of analytical model and numerical simulation with the experiment is presented. The analytical model successively describes the low frequency sound pressure field, while the numerical simulation is valid in the broader frequency range.